Sistem Pendukung Keputusan Berbasis Web Dalam Penentuan Susunan Personalia Organisasi Menggunakan Metode TOPSIS - Ahmadi Irmansyah Lubis; Dwi Amalia Purnamasari; Noper Ardi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The determination of the composition of personnel in an organization, especially in the activities of the Branch Conference (Musran) of the Muhammadiyah Branch Executive of Belian Village, is still done manually and tends to be subjective. This has the potential to cause inefficiencies and internal conflicts in the decision-making process. This research aims to develop a web-based decision support system (SPK) that can help the management selection process objectively by using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The TOPSIS method was chosen because it is able to provide the best alternative ratings based on its proximity to positive and negative ideal solutions. The five main criteria used in decision-making include: organizational experience, level of education, loyalty to the organization, leadership, and availability of time. The system is designed using the PHP programming language and MySQL database. The results of the implementation show that the system is able to produce recommendations for a more systematic, transparent, and accountable management structure. With this TOPSIS-based SPK, the deliberation process can run faster and more efficiently without eliminating the principle of democracy in the organization. This research is expected to be an innovative solution in adaptive and sustainable information technology-based organizational governance.